1993
DOI: 10.1080/02772249309357890
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of the organophosphorus pesticides chlorpyrifos, fenamiphos and vamidothion in water

Abstract: The photodegradation of the pesticides chlorpyrifos, fenamiphos and vamidothion in water containing 2-4% methanol was examined. Acetone (5%) was added as photosensitizer in the photolysis of vamidothion. A suntest apparatus equipped with a xenon arc lamp which exhibits a radiation very close to natural sunlight was employed. Analyses were performed by direct injection of the water samples containing the photoproducts into a liquid chromatograph with diode array and thermospray mass spectrometric detection. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
(21 reference statements)
1
27
1
Order By: Relevance
“…Novelty: Neither the detected and identified UV-induced degradation products of chlorpyrifos, nor its degradation pathway has not been described and observed so far. These degradates are not analogous with the results of Barcelo (1993) and Xu (2008): only 3,5,6-trichloro-2-pyridinol was found as the product of the biological degradation of chlorpyrifos by a newly isolated Paracoccus sp. strain TRP.…”
Section: Interpretation and Modelling Of Environmental Behaviour Of Dcontrasting
confidence: 64%
“…Novelty: Neither the detected and identified UV-induced degradation products of chlorpyrifos, nor its degradation pathway has not been described and observed so far. These degradates are not analogous with the results of Barcelo (1993) and Xu (2008): only 3,5,6-trichloro-2-pyridinol was found as the product of the biological degradation of chlorpyrifos by a newly isolated Paracoccus sp. strain TRP.…”
Section: Interpretation and Modelling Of Environmental Behaviour Of Dcontrasting
confidence: 64%
“…rescence at 620 nm. Upon photoexcitation, the excited 22 The photodegradation of vamidothion (vide supra) by state of the cation is quenched by S O to generate the 2 8 31 ?2 simulated sunlight has been studied in water / methanol strong oxidants Ru(bpy) and SO : 3 4 (2-4%) with 5% acetone added as a photosensitizer [64]. 21 21 The major photoproduct observed was vamidothion sulfox-…”
mentioning
confidence: 99%
“…According to Barron and Woodburn (1995) TCP is less toxic than chlorpyrifos. However, Barcelo et al (1993) and Baskaran et al (2003) reported higher toxicity of TCP as compared to its parent compound. TCP toxicity for a soil bacterium in Microtox system (EC 50 18.6 mg L −1 ) was 2.5 times higher than that of chlorpyrifos (EC 50 46.3 mg L −1 ) (Baskaran et al, 2003).…”
Section: Introductionmentioning
confidence: 86%